Factors Affecting to Consumers’ Attitude towards Halal Label on Nugget and Sausage Packaging: A Case Study on Housewives at One Residential in Yogyakarta City - Widodo Widodo; Siti Yusi Rusimah; Novita Choirunnisa (Universitas Muhammadiyah Yogyakarta, 2018)
Halal status of meat products is a credence attribute which is not visible and cannot be verified by consumers. Therefore, halal label is an important cue for consumers about the halal meat product. This study aimed to measure the consumers’ attitude and to clarify the demographic and psychological factors that affected the consumers’ attitude towards halal label on nugget and sausage packaging. The data of this study was collected in 2016 at one residential in Yogyakarta City. Meanwhile, respondents of 50 Muslim housewives were selected through simple random to fill out the self-administered questionnaire. To measure consumers’ information was used a 5 Likertscale of statement. While a binary logistic regression model was employed to analyse the effects of the demographic and psychological factors on consumers’ attitude. The results show that respondents of housewife perceived the label of council of certification, Arabic script of halal, and food ingredient could very well indicate the halal nature of nugget and sausage. Furthermore, respondents of housewife tend to use them to investigate the halal nature. The demographic factor which affected the variation of consumers’ attitude towards halal label was households’ expenditure of food, meanwhile the psychological factor which affected the variation of consumers’ attitude towards halal label was family habit of purchasing halal foods. Based on this results can be concluded that the respondents of housewife strongly believe on halal label on nugget and sausage packaging but they do not examine thoroughly. Respondent of housewife’s attitude toward halal label improved due to an increasing on households’ expenditure on food and a well family habituation.